2011
DOI: 10.1071/py10036
|View full text |Cite
|
Sign up to set email alerts
|

Factors that influence physical activity for pregnant and postpartum women and implications for primary care

Abstract: Many pregnant women and women of child-bearing age do not engage in the recommended levels of physical activity despite the well known benefits. Pregnancy and the postpartum period can be a time when inactivity actually increases. Women who experience gestational diabetes mellitus (GDM) during their pregnancy are often advised to become more active in order to ameliorate their increased risk of developing type 2 diabetes. Health professionals have an influential role in promoting physical activity, which would… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 22 publications
0
29
0
6
Order By: Relevance
“…Women themselves have identified that LTPA is an important aspect of postnatal well-being (Currie, 2009;Daley, MacArthur, & Winter, 2007). They also, however, report difficulties continuing with formal exercise in the postnatal period for various reasons including high stress levels (Lox & Treasure, 2000), lack of energy, feeling unwell, and lack of time and space for LTPA (Doran & Davis, 2011). Further, for some women, the expectations to achieve specified levels of LTPA in relation to frequency, intensity, and time can place an additional burden (e.g., feelings of mother guilt and inadequacy) on those who are already vulnerable and deemed "at risk, " including new mothers who are at particular risk of inactivity (Albright, Maddock, & Nigg, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…Women themselves have identified that LTPA is an important aspect of postnatal well-being (Currie, 2009;Daley, MacArthur, & Winter, 2007). They also, however, report difficulties continuing with formal exercise in the postnatal period for various reasons including high stress levels (Lox & Treasure, 2000), lack of energy, feeling unwell, and lack of time and space for LTPA (Doran & Davis, 2011). Further, for some women, the expectations to achieve specified levels of LTPA in relation to frequency, intensity, and time can place an additional burden (e.g., feelings of mother guilt and inadequacy) on those who are already vulnerable and deemed "at risk, " including new mothers who are at particular risk of inactivity (Albright, Maddock, & Nigg, 2006).…”
Section: Introductionmentioning
confidence: 97%
“…As ours and other studies suggest (see [30,33]), awareness of GDM as a risk factor for type 2 diabetes may not be sufficient to increase personal risk perception and motivate women to change their lifestyle and health behaviours. Other factors such as emotional stress and fear of diagnosis have been shown to present significant barriers to participation in follow-up health care programmes.…”
Section: Discussion/conclusionmentioning
confidence: 59%
“…For example, Kim et al . [30] and Doran and Davis [33] found that women with prior GDM who perceived themselves to be at high risk of developing type 2 diabetes and planned to modify their future health behaviour were also associated with the lowest fruit and vegetable consumption, and self-reported no physical activity (or any other recent modifications to their health or lifestyle behaviours). A small number of studies have used qualitative methodologies to explore the barriers to and facilitators of post-partum follow-up care in a cohort of women with recent GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the intervention designed from the formative research reported here can be used to inform how physical activity messaging is incorporated into Text4-baby in the future. The current Text4baby curriculum has limited SMS about physical activity, and because the evidence supporting participation in physical activity as part of a healthy pregnancy is ample [1][2][3][4][5][6][7][8][9][10][11][12], there is a need to modify standard Text4baby physical activity SMS in light of these findings.…”
Section: Original Researchmentioning
confidence: 99%
“…For the mother, benefits may include weight control [4] and reduced risk of early delivery and gestational diabetes [2,3,[5][6][7], and for the fetus, benefits may include improved stress tolerance and a decrease in resting fetal heart rate [8][9][10][11][12]. Despite these benefits, only 15.8 % of pregnant women (as compared to 26 % of non-pregnant women) achieve recommendations for physical activity [6,13,14] (i.e., meeting physical activity recommendations of 150 min of moderate intensity activity per week) [15][16][17].…”
Section: Introductionmentioning
confidence: 99%